COVID-19, adrenal gland, glucocorticoids, and adrenal insufficiency - Akbas, Emin Murat; Akbas, Nergis (Biomedical papers, 2021)
The current Coronavirus disease outbreak requires that physicians work in collaboration with other physicians especially in intensive care and emergency units. To fight against this new disease, whose pathogenesis, effects, and results have not been clearly demonstrated, especially in patients with the pre-existing chronic disease, requires special expertise and perspectives. Due to the need for dynamic glucocorticoid treatment at different stages of the disease in patients with adrenal insufficiency, the existence of reports indicating that "coronavirus disease 2019" also affects the adrenal reserve, and the use of glucocorticoids also in advanced stages in patients with Coronavirus disease require this issue to be emphasized with precision. Herein, treatment of the pre-existing adrenal insufficiency in patients with actual Coronavirus disease and the effects of the this critical disease on the adrenal gland have been reviewed.
Keywords: SARS-CoV-2; adrenal insufficiency; adrenal cortex; severe acute respiratory syndrome; glucocorticoids